Roman honor : the fire in the bones - Barton, Carlin A., 1948- (University of California Press, 2001)
This book is an attempt to coax Roman history closer to the bone, to the breath and matter of the living being. Drawing from a remarkable array of ancient and modern sources, Carlin Barton offers the most complex understanding to date of the emotional and spiritual life of the ancient Romans.